Implementing Pearson’s assessment framework in English language instruction: Insights from an Indonesian private high school - Zaki, Leil Badrah; Kezhiandra, Gabby; Akbar, Malik; Pratiwi, Theodesia Lady (Journal of Research on English and Language Learning (J-REaLL), 2026)
Structured assessment regimes are instrumental in influencing classroom teaching and learning. For example, an international curriculum, such as Pearson, provides structured assessment cornerstones for teaching and learning. Yet, despite Indonesian secondary schools widely adopting it, existing literature predominantly focuses on curriculum design and alignment, while the substantial issue of classroom-level impact resulting from standardized assessment demands still remains underexplored. The present paper seeks to uncover the extent to which Pearson's structured assessment requirements are realized in the classroom and how they impact teaching and learning. The qualitative case study research method was utilized through classroom observations and interviews concerning two foreign English teachers in a private secondary school in Batam, Indonesia. Results show that the Pearson assessment system, comprising mechanisms like the prohibition of homework, assessment by means of rubrics, and instant feedback, has brought in student engagement and reduced stress through steadiness and transparency in assessment. Nevertheless, strict timetables for exams and standard formats that are imposed on the teachers out of the core systems have led to a reduction of teachers' pedagogical freedom and an increase in their administrative workload. The systemic pressures, such as real-time assessment demands and rigid accountability structures, pose significant challenges, particularly in resource-constrained environments with diverse learner readiness. The study contributes to theoretical debates on standardized assessment by showing how tightly aligned frameworks compress pedagogical flexibility while demanding high instructional precision. The findings emphasize the need for more adaptable assessment frameworks that balance accountability and teacher autonomy as well as continuous student engagement.